Training In Takhrijul Hadith Competency Improvement Of Hadith Teachers At Baqiyatussa'adiyah Tembilan Hulu Islamic Boarding School - fiddian khairudin; Amaruddin , Amaruddin; Nasrullah , Nasrullah (KARYA ABDI, 2022)
Islamic boarding schools play an important role in developing studies of the sources of Islamic teaching, this hope is quite reasonable because the role of Islamic boarding schools in preserving Islamic studies is so great. This also happened to the Baqiyatussa’adiyah Islamic Boarding Schools, an Islamic educational institution located in Indragiri Hilir district, Riau province, precisely in Tembilahan Hulu sub-district. Some hadith problems sometimes stop in the process of memorizing and understanding their meaning, even though a complete and appropriate understanding will be found if it is refined by research on the hadith. Hadith research is important, one of the entrances is takhrijul hadis activities, namely the method of searching for hadith on the original source, where the hadith has been narrated complete with its sanad, then explain the level of quality of validity. To find alternative solutions to the problems, then takhrijul hadis training was held for ulumul hadis teachers, with the aim of training teachers to conduct research on the hadith which is the object of discussion, so that sufficient knowledge obtained about the source of hadith information and the original book where the hadith is listed. Another benefit is adding to the treasury of sanad through reference hadith books, clarification of the condition of the hadith, explain the quality of hadith, opinion of scholars on hadith, and so on. The terget audience for this community service is specifically teachers of hadith and in general the teachers of Baqiyatussaadiyah Islamic Boarding School. It is hoped that from this community service activity an increase in teacher skills will be obtained in conducting hadith research, especially in the takhrijul hadis steps.